2019
DOI: 10.1111/jam.14524
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactisharbouring Ara h 2.02 alleviates allergen‐specific Th2‐associated responses in sensitized mice

Abstract: Aim To study the prophylactic effect of recombinant Lactococcus lactis (rLl) harbouring Ara h 2.02 peanut allergen, in sensitized and challenged mice. Methods and Results Ara h 2.02 cDNA was cloned into pNZ8048 for heterologous expression in L. lactis. The purified recombinant allergen showed IgE binding comparable with native Ara h 2. Balb/c mice were fed with either recombinant (rLl), nonrecombinant L. lactis (Ll) or NaHCO3 (Sham) prior to sensitization and challenged with rAra h 2.02, whereas the baseline g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…IgE from all peanut allergic patients involved in the study recognized the E. coli -made rAra h 2; thus, authors reported this recombinant allergen as a promising candidate for its use in allergy diagnosis (Astier et al, 2006 ). Although tested with sera from peanut allergic mice, IgE-binding of natural Ara h 2 did not differ from those made in E. coli or L. lactis (Chan et al, 2020 ). Another study reported significantly weaker recognition of the E. coli -made rAra h 2 by IgE of allergic patients in comparison to the natural protein (Lew and Lim, 2016 ).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…IgE from all peanut allergic patients involved in the study recognized the E. coli -made rAra h 2; thus, authors reported this recombinant allergen as a promising candidate for its use in allergy diagnosis (Astier et al, 2006 ). Although tested with sera from peanut allergic mice, IgE-binding of natural Ara h 2 did not differ from those made in E. coli or L. lactis (Chan et al, 2020 ). Another study reported significantly weaker recognition of the E. coli -made rAra h 2 by IgE of allergic patients in comparison to the natural protein (Lew and Lim, 2016 ).…”
Section: Introductionmentioning
confidence: 82%
“…Isolated natural allergens have been largely replaced by recombinant allergens produced in prokaryotic hosts, mainly in Escherichia coli (Larsen et al, 2020 ) due to easier production, simpler characterization and standardization of the products, and the absence of cross-contamination with other allergens from the same source, which could influence the test results (Lowenstein and Larsen, 2001 ; Sancho et al, 2010 ; Curin et al, 2017 ). Escherichia coli and Lactococcus lactis have been utilized to produce rAra h 2 with low-to-moderate IgE-binding capacities (Astier et al, 2006 ; Lew and Lim, 2016 ; Chan et al, 2020 ). IgE from all peanut allergic patients involved in the study recognized the E. coli -made rAra h 2; thus, authors reported this recombinant allergen as a promising candidate for its use in allergy diagnosis (Astier et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%